Mechanical Characterization of the Interface Between a Shape Memory Alloy Fiber and a Resin Epoxy Matrix - Thiebaud, F.; Gabry, B.; Lexcellent, C. (Engineering Transactions, 1998)
The aim of this paper is to characterize the interface between a shape memory alloy wire (SMA) and an epoxy resin matrix. Here we present the effect of various surface treatments applied to SMA NiTi wires on the quality of the interface fiber/matrix. First, the use of the fiber pull–out test allows to separate the different treatments into two families: on the one hand, decohesion of the wire; on the other hand, rupture of the wire before debonding. The data given by the pull–out tests are not sufficient to differenciate the surface treatments which cause the breaking of the wire rather than the interfacial debonding of the fiber/matrix. In order to complete our research, a topographical study is carried out on different wires. It allows us to extract the parameters which characterize the vertical distribution of roughness and its morphology. The analysis of these experimental results leads to the choice of the surface treatment which will guarantee higher interfacial stresses. Among all the wires studied, we choose the prestrained wire. The quantitative aspect of this study allows us to know better the evolution of the different parameters of roughness, and thus to guide our research works to an optimal surface treatment of the wire.